THE LOSS FROM THE UPPER LAYER OF BOTTOM SEDIMENTS IN THE CORES FROM BOREHOLES BDP-96-1 AND BDP-96-2 (DRILLED ON LAKE BAIKAL) - Karabanov E.B.; Kuz'min M.I.; Geletii V.F.; Kalraychkov G.V.; Gvozdkov A.N. (My University, 1999)
In 1996, boreholes BDP-96-1 and BDP-96 penetrated the bottom sediments of Lake Baikal. From the lithological and geochemical correlation of the sediments, the loss from the upper layer of sediments in the cores is estimated: 630 cm (BDP-96-1) and 19 cm (BDP-96-2). Correlation of these cores with the 120 cm long core from borehole GC-1, taken with a gravity corer during the drilling through the lake ice, permits compilation of a general continuous record of climatic changes in Central Asia for the last 5 Ma and prevention of loss of Holocene sediments.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен